PENERAPAN KHIYAR DALAM SISTEM JUAL BELI BUAH DI QISYA BUAH ANDONOHU - Putri, Julia; Mahfudz, Mahfudz (IAIN Kendari, 2023)
Qisya Buah Andonohu is a fruit sales business whose sales process uses an offline and online buying and selling system. Buying and selling itself is an activity of exchanging goods for money, by relinquishing property rights from one to another. Meanwhile, online buying and selling is a buying and selling contract carried out using electronic means as a medium. When buying and selling activities take place in order to realize a good and honest transaction, it is best for the seller and buyer to apply khiyar in their buying and selling. Where khiyar is the perpetrator's right to choose to continue or cancel the transaction. In transaction activities there will definitely still be problems, the same thing happens in the buying and selling system at Qisya Buah Andonohu. The situation where buyers find that the fruit they have purchased is damaged or defective, this cannot be avoided considering that no matter how good or good the seller is at making sales, there will definitely be times when things will not be in accordance with the desired wishes. So the existing problems make it important to implement khiyar. Based on the background description, the problems that can be formulated are 1) what type of khiyar is applied at Qisya Buah Andonohu, and 2) how is khiyar applied at Qisya Buah Andonohu. This research uses a qualitative descriptive research method, the data collected is based on the results of observations, interviews and documentation carried out by researchers. The results of this research are that the buying and selling system carried out at Qisya Buah Andonohu, whether buying and selling offline or online, has implemented three types of khiyar in its buying and selling system. The Khiyar that have been applied to the buying and selling system at Qisya Buah Andonohu are Khiyar Majlis, Khiyar 'Aib, and Khiyar Terms.